Effect of nitrogen and phosphorus fertilization on perennial millet: influence on forage production and quality in the southeast of the Pampas (Semiárida, 2025)
The objective of this study was to evaluate the effect of nitrogen and phosphorus fertilization on the production and quality of Panicum coloratum L. (perennial millet), in a soil in southeastern La Pampa. The experiment was conducted on a perennial millet pasture in the town of Jacinto Arauz. The fertilization treatments were 0, 40 and 80 kg N ha-1 with and without P (fixed dose of 10 kg P ha-1) called: T- P- N40, N40+P- N80 and N80+P. The experimental design was randomized blocks with three replications. The accumulated dry matter (MSAC kg ha-1) (sum of three cuts during the growth cycle), the growth rate (TC, kg MS ha-1 day-1), the water use efficiency (EUA, kg MS ha-1 mm-1) and the apparent use of nitrogen (EUN) were quantified. In addition, deferred dry matter (DMS) and quality parameters were quantified: crude protein (PB) and dry matter digestibility (DMS). The response to fertilization in the MSAC showed increases with values of 51 % in the P treatment and 59 % with N80+P compared to the MSTD, indicating a greater response in biomass production in the MSAC compared to the MSTD. Nitrogen fertilization produced positive responses in forage production. The dose of 80 kg N ha-1 was the most effective during its growth cycle (MSAC). For deferred forage, the combination of 40 kg N ha-1 + P proved to be the best strategy. Nitrogen fertilization improved forage quality, with higher % of PB in treatments that only received N. The combination with N and P is a viable strategy to increase the production and quality of perennial millet in the Southeast of La Pampa.
Keywords: perennial pasture; productivity; forage quality